A 5D hyperchaotic Sprott B system with coexisting hidden attractors. (June 2016) - Ojoniyi, Olurotimi S.; Njah, Abdulahi N.
Abstract: A novel five-dimensional (5D) hyperchaotic Sprott B system with ten terms including two quadratic nonlinear and only one control parameter is presented. This system is algebraically simpler than Lorenz and Lorenz-like 5D systems with twelve terms, three quadratic nonlinear including five or six control parameters. It is of interest to note that the 5D system has hidden attractors over the entire single control parameter space, apart from this, the only control parameter present also shows coexisting hidden hyperchaotic, symmetric chaotic and periodic attractors spread over the parameter space which have not been observed in any reported 5D hyperchaotic system. Numerical simulations of the dynamics of the proposed system are done with the Lyapunov exponents spectrum, Lyapunov dimensions, bifurcation diagrams, Poincare sections and phase space orbits.